HOPE and AMPK activation reduce reperfusion injury and metabolic dysfunction in primate steatotic liver grafts - Tao Li; Pengkang Chang; Yimeng Wang; Yihong Song; Pengxiang Qu; Bo Wang; Yi Lyu; Liangshuo Hu (Scientific Reports)
Abstract Living liver transplantation has become a significant and evolving aspect of organ transplantation, with a notable proportion of cases involving pediatric patients. Metabolic-associated fatty liver disease (MAFLD) is the most prevalent chronic liver disease. The growing number of individuals with MAFLD has led to an annual increase in the proportion of non-alcoholic fatty liver donors for pediatric living liver transplantation. Hypothermic oxygenated perfusion (HOPE) has been demonstrated to improve graft quality through the implementation of a continuous mechanical perfusion cycle. However, there is currently a paucity of evidence regarding its ability to reduce steatosis and improve prognosis within a shorter time window of living-organ transplantation, especially in primate models. This study simulated steatotic liver grafts in living liver transplantation using the MAFLD model of the cynomolgus monkey and explored the effects of HOPE combined with the AMPK activator AICAR on the amelioration of the donor liver. The left outer lobe livers were statically cold preserved for two hours, subjected to HOPE for two hours, or treated with HOPE + AICAR (1 mmol/L) for two hours, respectively. Subsequently, a normothermic ex vivo reperfusion model (IRM) simulating post-transplant reperfusion was established using diluted autologous blood. Following simulated reperfusion in vitro, steatotic liver grafts in the static cold preservation group exhibited notable reperfusion injury. The degree of reperfusion injury induced by the remaining two groups was reduced, with the HOPE + AICAR group showing the most significant reduction (P < 0.05). The adenosine triphosphate (ATP) level of the hepatic tissues in the HOPE + AICAR group was observed to improve at two hours of reperfusion, exhibiting a significantly higher level than that in the cold-preserved group (P < 0.05). Furthermore, the HOPE + AICAR group exhibited a notable decline in MDA levels (P < 0.05), accompanied by a considerable reduction in 8-OHdG and lactate concentrations in both the liver tissue and perfusate. Additionally, there was a marked decrease in the release of TNF-α and IL-6 cytokines, along with a reduction in TLR-4 activation (P < 0.05). In comparison to the cold-preserved and HOPE groups, the HOPE + AICAR group demonstrated the capacity to alter the degree of steatosis following a two-hour treatment period, as evidenced by a notable reduction in liver tissue triglyceride and cholesterol levels (P < 0.05). Additionally, p-AMPK levels in liver tissue were significantly increased in the HOPE + AICAR group (P < 0.05). The combination of HOPE and AMPK activators has been shown to reduce the degree of steatotic liver grafts in a relatively short time, significantly reduce reperfusion injury, and improve liver function. This study contributes to the existing body of knowledge on mechanical perfusion in primate models, addressing a previously identified gap in the literature.